Replication of a Nuclear Polyhedrosis Virus in a Continuous Cell Culture of Spodoptera frugiperda: Purification, Assay of Infectivity, and Growth Characteristics of the Virus - Knudson, D. L. (1974)
Nonoccluded virus, polyhedra, and occluded virus were purified from a continuous cell culture of Spodopera frugiperda infected with nuclear polyhedrosis virus. The optimal temperature for the replication and lateral transmission of infectivity for the nuclear polyhedrosis viruses (NPV) in cell culture was 27 C. End-point dilution and plaque assay procedures for the measurement of infectivity are described and compared. Dose-response data demonstrated that a single particle could initiate an infection, and the validity of the relationship of 0.7 PFU per mean tissue culture infective dose (TCID(5 0)) further substantiated the accuracy of these infectivity assays. Particle-infectious unit calculations gave a ratio of 62 to 310 nonoccluded virus particles TCID(5 0). Growth cycle and lateral transmission experiments indicated that infectious material was released from cells 12 h postinfection (p.i.) and approached a maximal titer 4 days p.i. The number of polyhedra, nonoccluded virions, and TCID(5 0) produced per cell was also presented. Typical yields of NPV produced per liter flask suggested that insect cell culture systems represent a feasible means by which the replication of these viruses could be investigated.